2014
DOI: 10.4103/1008-682x.124560
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among androgen receptor CAG repeat polymorphism, sex hormones and penile length in Han adult men from China: a cross-sectional study

Abstract: This study aimed to investigate the correlations among androgen receptor (AR) CAG repeat polymorphism, sex hormones and penile length in healthy Chinese young adult men. Two hundred and fifty-three healthy men (aged 22.8 ± 3.1 years) were enrolled. The individuals were grouped as CAG short (CAGS) if they harbored repeat length of ≤20 or as CAG long (CAGL) if their CAG repeat length was >20. Body height/weight, penile length and other parameters were examined and recorded by the specified physicians; CAG repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Relationship between the length of AR (CAG)n and current testosterone levels is somewhat inconsistent referring to the previous studies in males: The four studies indicate that the length is positively correlated with the levels (De Naeyer et al, ; Ma et al, ; Manuck et al, ; Stanworth, Kapoor, Channer, & Jones, ); another study, however, demonstrates a significant negative correlation between them (Mosaad, Shahin, Elkholy, Mosbah, & Badawy, ); and another 15 studies report there is no a significant correlation between them at all (Aluja et al, ; Durdiaková et al, ; Durdiaková et al, ; Eisenegger, Kumsta, Naef, Gromoll, & Heinrichs, ; Gettler et al, ; Goutou, Sakka, Stakias, Stefanidis, & Koukoulis, ; Hampson & Sankar, ; Kubranska et al, ; Lapauw, Goemaere, Crabbe, Kaufman, & Ruige, ; Nowak, Diamond, Land, & Moffat, ; Ryan et al, ; Sankar & Hampson, ; Schneider et al, ; Schneider, Zitzmann, Gromoll, Ladwig, & Berger, ; Stiger et al, ). Regarding the same relationship analyzed by previous studies for females, two studies indicate the length is positively correlated with the levels (Peng et al, ; Skrgatic, Baldani, Cerne, Ferk, & Gersak, ); such relationship, however, is significantly negative (Brum et al, ; Jaaskelainen et al, ); or not significant (Durdiaková et al, ; Jaaskelainen, Korhonen, Voutilainen, Hippelainen, & Heinonen, ; Nowak et al, ).…”
Section: Study 3: the Relationship Between Ar(cag)n With Current Testmentioning
confidence: 92%
“…Relationship between the length of AR (CAG)n and current testosterone levels is somewhat inconsistent referring to the previous studies in males: The four studies indicate that the length is positively correlated with the levels (De Naeyer et al, ; Ma et al, ; Manuck et al, ; Stanworth, Kapoor, Channer, & Jones, ); another study, however, demonstrates a significant negative correlation between them (Mosaad, Shahin, Elkholy, Mosbah, & Badawy, ); and another 15 studies report there is no a significant correlation between them at all (Aluja et al, ; Durdiaková et al, ; Durdiaková et al, ; Eisenegger, Kumsta, Naef, Gromoll, & Heinrichs, ; Gettler et al, ; Goutou, Sakka, Stakias, Stefanidis, & Koukoulis, ; Hampson & Sankar, ; Kubranska et al, ; Lapauw, Goemaere, Crabbe, Kaufman, & Ruige, ; Nowak, Diamond, Land, & Moffat, ; Ryan et al, ; Sankar & Hampson, ; Schneider et al, ; Schneider, Zitzmann, Gromoll, Ladwig, & Berger, ; Stiger et al, ). Regarding the same relationship analyzed by previous studies for females, two studies indicate the length is positively correlated with the levels (Peng et al, ; Skrgatic, Baldani, Cerne, Ferk, & Gersak, ); such relationship, however, is significantly negative (Brum et al, ; Jaaskelainen et al, ); or not significant (Durdiaková et al, ; Jaaskelainen, Korhonen, Voutilainen, Hippelainen, & Heinonen, ; Nowak et al, ).…”
Section: Study 3: the Relationship Between Ar(cag)n With Current Testmentioning
confidence: 92%
“…In our study, short (≤22 CAG) and long CAG (>22 CAG) repeat groups showed no significant difference in the infertility risk. On the The association of CAG repeats with the serum levels of LH, FSH, testosterone and testicular volume demonstrates contradictory results in several studies, most of which did not find a significant correlation between several hormones and CAG repeats (Badran et al, 2009;Ma et al, 2014;Sasagawa et al, 2001). In our study, we also could not find any correlations between the CAG repeat expansion and levels of testosterone, LH and FSH.…”
Section: Discussionmentioning
confidence: 99%